Driving Agribusiness MSME Performance: Linking Service Quality to Innovation Capability - Usman, Agus; Windarko, Windarko (IJBLE Scientific Publications Community Inc., 2026)
This study examines the effect of service quality on small and medium-sized enterprise (SME) performance, with innovation capability serving as a mediating variable. A quantitative research design was employed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The study involved owners and managers of SMEs operating in the processed food sector based on agricultural commodities. Data were collected through a structured questionnaire and analysed using SmartPLS version 4. The results demonstrate that service quality has a significant positive effect on SME performance and acts as a key driver of innovation capability. Furthermore, innovation capability significantly mediates the relationship between service quality and performance, indicating that SMEs are able to convert superior service quality into improved performance outcomes through enhanced innovation. These findings highlight the strategic role of innovation capability in strengthening the impact of service quality on business performance. This study contributes to the literature by providing empirical evidence from agribusiness-based SMEs and emphasizing innovation as a critical factor for achieving sustainable competitiveness at both local and global levels. The findings offer important managerial implications for SME practitioners and policymakers in designing strategies that integrate service excellence with innovation development.